Pengaruh Work Life Balance dan Organizational Justice Terhadap Kinerja Karyawan dengan Organizational Citizenship Behavior Sebagai Variabel Mediasi - Suyoto; Taufiq Ali Susanto; Alfato Yusnar Kharismasyah; Tri Septin Muji Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research aims to examined the effect of work life balance and organizational justice on employee performance with organizational citizenship behaviour as a mediating variable. The population in this study were employees of the Banyumas Land Office. This research applies a quantitative approach method. The sample used amounted to 110 employees and the respondents were obtained using non probability sampling with purposive sampling. The type of data in this study is primary data and the instrument used in data collection is a questionnaire with a 5-point Likert scale measurement. While the analysis technique used is SEM PLS version 3.0. The results showed that work life balance and organizational justice had a positive and significant effect on organizational citizenship behavior, work life balance and organizational justice had a positive and significant effect on employee performance, organizational citizenship had a positive and significant effect on employee performance, organizational citizenship behavior mediated the effect of work life balance on employee performance. However, organizational citizenship behavior cannot mediate the influence of organizational justice on employee performance.